A rare case of spontaneous abdominal aorta thrombosis - Ahmad Samir Matarneh (14777680) (2021)
Spontaneous aortic thrombosis is rare, and prompt diagnosis is needed whenever encountering a case of unexplained abdominal pain. The cause of the thrombosis needs to be evaluated thoroughly to rule out any underlying thrombophilias. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4571